PERANCANGAN SISTEM E-LEARNING DENGAN INTEGRASI CHATBOT ARTIFICIAL INTELLIGENCE DI UNIVERSITAS BANTEN JAYA - Andi Usri Usman; Korneilis; Rehulina Tarigan; Ismail Husun (Journal of Innovation And Future Technology, 2026)
The development of information technology presents great opportunities to improve the quality of higher education, particularly in addressing the challenges of accessibility to learning materials for students with limited time, such as evening class participants and working students. This study aims to design a web-based e-learning system at Universitas Banten Jaya, equipped with an artificial intelligence–based chatbot integrated through the Gemini AI Application Programming Interface (API). The proposed system provides features for uploading and managing learning materials in a structured manner, multiple-choice quizzes as tools for assessing students understanding, and periodic learning progress monitoring accessible to lecturers and administrators. In addition, the system allows students to provide evaluations of lecturers after completing learning materials to improve teaching quality. The development method employs an Agile approach, enabling iterative and responsive system development based on user needs. The result of this study, in the form of a system design, is expected to serve as a foundation for developing an effective and efficient e-learning system at Universitas Banten Jaya, enhancing material accessibility, supporting independent learning processes, and assisting lecturers in managing and monitoring learning activities. This research contributes to the development of innovative educational technology that is user-oriented and responsive to the needs of the higher education environment.